NF-κB mediated regulation of tumor cell proliferation in hypoxic microenvironment - Rastogi, Shubham; Aldosary, Sara; Saeedan, Abdulaziz S.; Ansari, Mohd. Nazam; Singh, Manjari; Kaithwas, Gaurav (Frontiers in Pharmacology, 2023)
Hypoxia is caused by a cancer-promoting milieu characterized by persistent inflammation. NF-B and HIF-1 are critical participants in this transition. Tumor development and maintenance are aided by NF-B, while cellular proliferation and adaptability to angiogenic signals are aided by HIF-1. Prolyl hydroxylase-2 (PHD-2) has been hypothesized to be the key oxygen-dependent regulator of HIF-1 and NF-transcriptional B's activity. Without low oxygen levels, HIF-1 is degraded by the proteasome in a process dependent on oxygen and 2-oxoglutarate. As opposed to the normal NF-B activation route, where NF-B is deactivated by PHD-2-mediated hydroxylation of IKK, this method actually activates NF-B. HIF-1 is protected from degradation by proteasomes in hypoxic cells, where it then activates transcription factors involved in cellular metastasis and angiogenesis. The Pasteur phenomenon causes lactate to build up inside the hypoxic cells. As part of a process known as lactate shuttle, MCT-1 and MCT-4 cells help deliver lactate from the blood to neighboring, non-hypoxic tumour cells. Non-hypoxic tumour cells use lactate, which is converted to pyruvate, as fuel for oxidative phosphorylation. OXOPHOS cancer cells are characterized by a metabolic switch from glucose-facilitated oxidative phosphorylation to lactate-facilitated oxidative phosphorylation. Although PHD-2 was found in OXOPHOS cells. There is no clear explanation for the presence of NF-kappa B activity. The accumulation of the competitive inhibitor of 2-oxo-glutarate, pyruvate, in non-hypoxic tumour cells is well established. So, we conclude that PHD-2 is inactive in non-hypoxic tumour cells due to pyruvate-mediated competitive suppression of 2-oxo-glutarate. This results in canonical activation of NF-kB. In non-hypoxic tumour cells, 2-oxoglutarate serves as a limiting factor, rendering PHD-2 inactive. However, FIH prevents HIF-1 from engaging in its transcriptional actions. Using the existing scientific literature, we conclude in this study that NF-B is the major regulator of tumour cell growth and proliferation via pyruvate-mediated competitive inhibition of PHD-2.